Pelvic Floor Nonrelaxation: Approach to Evaluation and Treatment - Kaplan, Jennifer A.; Simianu, Vlad V. (Clinics in Colon and Rectal Surgery, 2020)
Dyssynergic defecation can be a complex, burdensome condition. A multidisciplinary approach to these patients is often indicated based on concomitant pathology or symptomatology across the pelvic organs. Escalating treatment options should be based on shared decision making and include medical and lifestyle optimization, pelvic floor physical therapy with biofeedback, Botox injection, sacral neuromodulation, rectal irrigation, and surgical diversion.
Keywords: anismus; Botulinum toxin; dyssynergic defecation; pelvic floor; sacral neuromodulation